HOW EASY AND SAFE IS QRIS? UNCOVERING THE FACTORS THAT DRIVE USER INTEREST IN PEMATANGSIANTAR - Lora Ekana Nainggolan; Nana Triapnita Nainggolan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study confirms that the benefits and ease of use of QRIS directly encourage public interest in transacting MSME products in Pematangsiantar City. Using a quantitative research method with 100 respondents, the data were analysed using SmartPLS to examine the relationships among variables. The results show that the greater the benefits and the easier QRIS is to use, the greater users' interest in choosing digital transactions. Another important finding is the crucial role of user experience (UX), which has been shown to amplify the influence of these benefits and conveniences. Intuitive UX, simple interface, and clear transaction processes can reduce potential barriers and increase the adoption of financial technology. In addition, the digital footprint of each transaction also strengthens the sense of security and trust between users and MSME actors. More broadly, this research makes a strategic contribution to accelerating Indonesia's digital economy transformation. With increased transparency and efficiency of MSME transactions, the flow of money remains in the country, thereby strengthening public awareness and supporting economic independence. These findings affirm the urgency of enhancing digital infrastructure and improving UX quality to expand the use of QRIS in society.